Hyptis brevipes (Lamiaceae) Extracts Strongly Inhibit the Growth and Development of Spodoptera littoralis (Boisd.) Larvae (Lepidoptera: Noctuidae) - Hanem H. Sakr, Shimaa H. Roshdy and Hesham R. El-Seedi & (Journal of Applied Pharmaceutical Science, 2013)
Hyptis brevipes (Lamiaceae) extracts are shown to exhibit strong insecticidal activity against the 3rd instar larva of the cotton leaf worm Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae), inducing complete larval mortality due to the arrest and/or disruption of metamorphosis. This disruption induced a wide range of abnormalities. The LC50 value of the dichloromethane extract of H. brevipes was 3.0% (95% F.L. = 2.2% - 4.4%; slope = 3.185± 0.952) after three days of treatment. Two active compounds were isolated from the extract following bioassay-guided fractionation and were identified as 5-hydroxy-7,4'-dimethoxy-flavon-3-ol and 5-hydroxy-7-methoxy-2-(4`-methoxy-phenyl)-chromen-4-one based on spectroscopic data. This is the first report of these secondary metabolites in H. brevipes.
Keywords: Hyptis brevipes, Lamiaceae, Spodoptera littoralis, growth disruption, flavonoids.